Effect of Dietary Fiber Sources on In-Vitro Fermentation and Microbiota in Monogastrics - Ngalavu, Asavela (Animals (Basel), 2020)
SIMPLE SUMMARY: The recent findings on the role played by fiber constituents during digestion remain controversial, while the impact of high fiber feeds on digestion depends on the type, form, and the level of inclusion of fiber in the diet. This study aims to determine the effect of different fiber forms in pig diets on intestinal nutrient digestibility, hindgut fermentation, and microbial community composition. We formulated four experimental groups (group A = alfalfa, group B = corn stalk, group C = rice straw, and group D = controls) to evaluate the effect of dietary fiber sources on in-vitro fermentation and microbiota. Cornstalk showed a high digestibility when compared to alfalfa and rice straw. Greater digestibility of corn stalk than rice straw and alfalfa in these results may be due to the lower crude fiber content in corn stalk when compared to alfalfa and rice straw. In conclusion, corn stalk dietary fiber improved dry matter digestibility in simulated in vitro digestion experiments, whereas rice straw fiber improved volatile fatty acid content in simulated in vitro digestion and fermentation efficiency. Furthermore, alfalfa fiber improved the thickness of Firmicutes and Lactobacillus supernatant in simulated in vitro digestion treatments. ABSTRACT: Feed fiber composition is usually considered as one of the factors that have an impact on digestive tract microbiota composition. The investigations on the level of fermentation and in-vitro digestibility of different fibers are not well understood. The aim of the current study is to determine the effect of different fiber sources on intestinal nutrient digestibility, hindgut fermentation, and microbial community composition under in vitro conditions using pigs’ hindgut as a model. The experimental treatment diets contained alfalfa hay, cornstalk, and rice straw. Cornstalk treatment displayed higher digestibility compared to alfalfa hay and rice straw; similar results were observed with in-vitro digestibility using intestinal digesta. Firmicutes were the most abundant phyla (Firmicutes = 89.2%), and Lactobacillus were the prominent genera (75.2%) in response to alfalfa compared to rice straw and cornstalk treatments. In simulated in-vitro digestion, corn stalk fiber improved dry matter digestibility; rice straw fiber improved volatile fatty acid content and fermentation efficiency. Alfalfa fiber improved the thickness of deposited Firmicutes and Lactobacillus.